Enhanced brightness and efficiency of organic light-emitting diodes with an LiF in the Alq(3) - Kim, Young Min; Lee, Joo Won; Jung, Jae Hoon; Paek, Kyeong-Kap; Sung, Man Young; Kim, Jai Kyeong; Ju, Byeong Kwon (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2006)
Highly efficient and bright organic light-emitting diodes have been realized by inserting a thin insulating lithium fluoride (LiF) layer in the tris-(8-hydroxyquinoline) aluminum (Alq(3)) with conventional organic layers. By comparing the performances of newly devised devices as a function of the position of the LiF in the Alq(3) layer, the authors propose the optimal position of the LiF in the Alq(3) layer. Experimental results show that the efficiency and brightness of the newly devised device with LiF in the Alq(3) layer were seven times higher than that without LiF in the Alq(3) layer.
Keywords: ELECTROLUMINESCENT DEVICES; LAYER; INTERFACE; TRANSPORT; CHARGE